Public perception of COVID-19 in Saudi Arabia during the Omicron wave: recommendations for policy improvement - Almalki, Mohammed J.; Alotaibi, Amani A.; Jabour, Abdulrahman M.; Elamin, Ali; Hetany, Wafa A; Adam, Hamza Abdullah M.; Moafa, Hassan N; Alamer, Ahmed S.; Alsharif, Anwar; Almalki, Sami M. (Frontiers in Public Health, 2025)
With the emergence of new SARS-CoV-2 variants, it is difficult to forecast potential epidemiological changes. This study investigates Saudi citizens' perceptions of COVID-19 during the Omicron wave.We used an online survey with a convenience sample of 746 participants, employing a cross-sectional study design. The survey included questions about demographics, anxiety level, perception of COVID-19 during the Omicron wave, and open-ended space.Our findings indicate that 27.3% of the participants believed that COVID-19 cases would decrease, 30.2% believed that cases would increase, and 42.5% were uncertain about their perceptions. When asked about the main reasons for their expectation of a rise in COVID-19 cases, the top two causes reported by participants were non-adherence to prevention measures (74.7%) and the high transmissibility of the virus (66.7%). On the other hand, when asked about the reasons for their expected decrease in COVID-19 cases, participants cited the availability of free vaccines (60.3%), government measures (59.9%), compliance with preventive measures (57.4%), and health awareness programs (44.1%). Multivariate logistic regression analysis indicated that anxiety about COVID-19 (AOR = 1.23, 95% CI: 1.15 -1.32) and education level (AOR = 1.58, 95% CI: 1.11 -2.25) significantly predicted respondents' perceptions regarding an expected increase in COVID-19 cases (P < 0.05). Around 46.2% of participants reported moderate to high worry levels about re-lockdown, and 36.2% reported moderate to high anxiety. Ordinal logistic regression analysis showed that respondents who reported higher levels of worry about re-lockdown were 1.28 times more likely to experience higher anxiety levels regarding COVID-19 (P < 0.05). Unexpectedly, a few participants were unwilling or hesitant to follow preventive measures because they believed that COVID-19 was not real or risky or they had already been vaccinated. This finding is concerning because it suggests that some people are not taking the threat of COVID-19 seriously.This study offers significant insights into how Saudi citizens viewed the situation of COVID-19 during the Omicron wave. These insights can help shape public health policies and resources, control the potential spread of viral variants, and prepare for future pandemic risks. Additionally, action for policy improvement is presented.